1989
DOI: 10.1159/000205377
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Thrombocytopenic Purpura: Report of a Case with a Possible Response to High-Dose Intravenous Gamma Globulin

Abstract: The case history of a 71-year-old woman with three episodes of a microangiopathic hemolytic anemia over a 22-year span is detailed. During the last episode a possible response of her thrombotic thrombocytopenic purpura (TTP)-like syndrome to the administration of intravenous immunoglobulin is documented. In retrospect it became apparent that she only improved in her prior episodes after receiving plasma-containing blood products. Prior case reports of TTP responses to intravenous immunoglobulin are reviewed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…Contrary to a small number of case studies [13, 14, 15, 16, 17]reporting a beneficial effect of high-dose ivIGg, two subsequent studies [22, 23], where 3 and 17 patients were included respectively, are in agreement with us that there is no benefit by the addition of ivIgG to standard modalities. This is the largest study in TTP patients where 29 patients received ivIgG in addition to standard treatment and were compared to 15 patients receiving standard treatment alone.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Contrary to a small number of case studies [13, 14, 15, 16, 17]reporting a beneficial effect of high-dose ivIGg, two subsequent studies [22, 23], where 3 and 17 patients were included respectively, are in agreement with us that there is no benefit by the addition of ivIgG to standard modalities. This is the largest study in TTP patients where 29 patients received ivIgG in addition to standard treatment and were compared to 15 patients receiving standard treatment alone.…”
Section: Discussionsupporting
confidence: 65%
“…However, their efficacy has not been clearly shown yet. The rationale for the use of immunoglobulins was based on the following: (a) It had been previously shown that both homologous and autologous platelet aggregation by plasma of TTP patients can be inhibited by normal adult IgG in vitro [11, 12], and (b) There had been sporadic cases published in the literature reporting the efficacy of ivIgG in inducing remission in TTP patients who had previously failed on the standard treatment with plasma exchange [13, 14, 15, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Other therapies reported in Jehovah's Witness (JW) patients with TTP, such as plasmapheresis using hydroxyethylstartch [8] or a plasma substitute, Gelofusine [9] were avoided due to the patients severe anemia. We elected to manage this patient's TTP with IVIG and steroids based on case reports describing successful management of TTP with IVIG [10].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, IVIG was tried for TTP before PE became the first-line treatment. There have been some successful reports of IVIG therapy for TTP, including PE-or plasmainfusion-refractory cases: two children and 12 adults [16][17][18][19][20]. In summary, ten of those 14 patients responded to IVIG and achieved complete remission.…”
Section: Discussionmentioning
confidence: 99%